Seismic sequence stratigraphy of a foreland unit in the Magallanes-Austral Basin, Dorado Riquelme Block, Chile: implications for deep-marine reservoirs (Latin American Journal of Sedimentology and Basin Analysis, 2021)
This contribution presents geological data that provides a sequence-strati- graphic-based exploration model for Oligocene units in the central Magallanes-Austral Foreland Basin, and identifies the related sedimentary deposits that constitute basin- floor fan reservoirs. The study area is located in the Magallanes Region, Chile, and it was discovered in 2009-2010 by the joint venture of the National Oil Company of Chile and Methanex group at Dorado Riquelme Block. Seismic stratigraphic analysis of the Magallanes-Austral Foreland Basin enabled the definition of four evolutionary stages using 3D seismic information from a 91.6 km long section, as well as lithostratigraphic and biostratigraphic records and wireline logs. The clinoforms observed in the Foreland III stage of the Magallanes-Austral Foreland Basin are the focus of this study. Six seismic units (SU-1 to SU-6) and twenty-five depositional sequences were identified there, based on temporal affinity and genetic mechanisms. The youngest four seismic units comprise alternating forestepping and downstepping prograding patterns, while the fifth seismic unit is characterized by a backstepping pattern, which is followed by a sixth seismic unit in which forestepping patterns are again developed. The most important reservoirs were identified in seismic unit SU-2, and they are associated with sandstone-prone deposits accumulated in basin-floor fans. Their development is associated in this contribution with periods of relative sea-level fall during forced regressions.